Discourses of identity in liminal places and spaces
1 online resource.
Keywords: This collection highlights the interplay between language and liminal places and spaces in building distinct narratives of selfhood. The book uses an interdisciplinary approach to examine linguistic and social phenomena in places shaped by displacement and social inequality. The book alsolooks atchronotopes, the Bakhtinian-inspired concept of the interconnectedness of time and space in identity. The volume demonstrates how studyingliminal places and spaces can offer unique insights into how people constructlanguage and selfhood in these spaces,making this key reading for researchers in sociolinguistics, discourse analysis, geography, and linguistic anthropology.